Evaluation of the performance of five hybrid water yam clones in the yam belt of Nigeria - Ikeorgu, J.G.; Egesi, Chiedozie N.; Asiedu, Robert (International Institute of Tropical Agriculture, 2010)
The performance of 5 promising pre-release hybrid water yam (D. alata) varieties (TDa 98/01166; TDa 98/01176; TDa 98/01168; TDa 99/91169; and TDa 99/00240) evaluated for high and stable yields, pest and disease resistance and desirable food qualities, was determined in 2004 and 2005 in 6 locations in the Nigerian yam belt. The trials were laid out in randomized complete block design in three replications in each location. The results from two year fresh tuber yield and disease severity scores show that four of the hybrid water yams (TDa 99/00240; 98/01176, TDa 98/01166 and 98/01168 performed significantly better than the two local best checks (UM 680 and Sudan) They were also moderately resistant to the major pests and diseases of water yams. Fresh tuber yield of TDa 99/01169 was only as good as the local cultivars but based on farmer preference rating of the eating qualities of the varieties, TDa 99/01169 was as good as the local cultivars which were most preferred. All the hybrid water yam genotypes were rated as good as the landraces in farmer preference.